Indonesian Blogger Analyzing Bjorka Hacker - M. Jacky; FX Sri Sadewo (Technium Social Sciences Journal, 2023)
Indonesia is a target for international hackers. Weak public data security systems and the negligence of those who are authorized to guard data are used by hackers. Sensitive citizen data such as identity cards, family card numbers, cell phone numbers, passport numbers, and so on are weighted by Bjorka hackers. The Indonesian government found it difficult to arrest Bjorka and even arrested several times the wrong person he thought was Bjorka. This research tries to describe bloggers in Indonesia in an effort to clarify the figure of Bjorka. Researchers use Discourse/Non-Discourse Analysis. Indonesian bloggers believe that Bjorka is not a foreigner. By analyzing Indonesian Bjorka English, bloggers find Indoglish: “because since,” “a noise,”. Bjorka’s excessive knowledge of Indonesians per case also indicates that he is part of Indonesia. He knows about the Munir, Denny Siregar, Puan Maharani, and Permadi Arya cases. Bjorka has higher political motives than economic ones. Bjorka’s actions are not just data theft. He is part of a political game that is not visible to the eye. Bjorka was part of a power struggle.